The French worker : autobiographies from the early industrial era - Traugott, Mark (University of California Press, 1993)
This anthology, drawn from the autobiographies of seven men and women whose lives span the nineteenth century, provides a rare glimpse of the everyday lives of workers in the age of early industrialization in France. Appearing for the first time in English, these stories vividly convey the ambitions, hardships, and reversals of ordinary people struggling to gain a measure of respectability. The workers' livelihoods are diverse: chair.